Grain and Seed Proteins Functionality 2021
DOI: 10.5772/intechopen.95873
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inadequate Concentration of Boron in Seed Storage Proteins Content in Oilseed Crops

Abstract: For the estimation of Impact of inadequate concentration of boron in seed storage proteins content in oilseed crops, a sand culture experiment was designed and all the three crops i.e. soyabean, mustard and linseed were grown under sufficient and insufficient boron treatment till maturity. Seed germination and seed storage protein concentration was determined in seeds after the harvesting of crops. Earlier oilseed crops like soyabean, mustard and linseed are cultivated for oil production but at this time these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Although the effect of nutrients in deposition and mobilization of protein reserves in seeds is not fully understood, it is believed that Ca +2 and Mg +2 cations contribute to these events to happen (Santos et al, 2012), which was observed for albumins, which was the protein found in greatest amount in sweet pepper seeds (Table 2). Archana et al (2021) studied the effects of boron doses on the expression of proteins (albumin, globulin, glutelin and prolamin) and on the quality of seeds of several species, reporting that at higher doses there were signs of boron toxicity, which caused low protein expression, resulting in low seed quality. Reis et al (2020), in rice seeds, also found a relationship between protein content and seed physiological quality.…”
Section: Resultsmentioning
confidence: 99%
“…Although the effect of nutrients in deposition and mobilization of protein reserves in seeds is not fully understood, it is believed that Ca +2 and Mg +2 cations contribute to these events to happen (Santos et al, 2012), which was observed for albumins, which was the protein found in greatest amount in sweet pepper seeds (Table 2). Archana et al (2021) studied the effects of boron doses on the expression of proteins (albumin, globulin, glutelin and prolamin) and on the quality of seeds of several species, reporting that at higher doses there were signs of boron toxicity, which caused low protein expression, resulting in low seed quality. Reis et al (2020), in rice seeds, also found a relationship between protein content and seed physiological quality.…”
Section: Resultsmentioning
confidence: 99%
“…A large amount of Seed storage 2S albumin superfamily protein is synthesized at the late stage of seed development [52,53]. The protein content and the degradation rate of stored protein are closely related to seed vigor [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, a consistent increase in ω-gliadin was found from 0 to 50 kg ha –1 , while γ-gliadin and HMW-GS/LMW-GS ratios showed the opposite trend . Zinc application increased the total protein content, protein composition, and subfractions in both wheat and cowpea, except for globulin and the gliadin/glutenin ratio in wheat. , Positive effects of boron on the total protein content and protein composition were pronounced in soybean, mustard, and linseed …”
Section: Nutrients Involved In Storage Protein Biosynthesis Content A...mentioning
confidence: 99%